(untitled) - Coche, A. G. (Rome, 1989)
Topographical surveys - plan surveying, topographical surveys - direct levelling, topographical plans and maps, measurement of areas and then topography and freshwater fish culture.
Keywords: Topographical surveying,Fish-culture,Khảo sát địa hình,Nuôi cá nước ngọt